2013
DOI: 10.1111/apt.12488
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: rectal indomethacin for the prevention of post-ERCP pancreatitis

Abstract: SUMMARY BackgroundDespite initial evidence in the literature, nonsteroidal anti-inflammatory drugs (NSAIDs) have not been widely used to prevent post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 25 publications
1
49
1
Order By: Relevance
“…Number needed to treat was 20. Moreover they found that in subgroup analysis, the difference remained unchanged for average-risk population [OR = 0.49 (0.28-0.85); P = 0.01] or in preventing severe PEP [OR = 0.41 (0.21-0.78); P = 0.007] [50] . The European Society of Gastrointestinal Endoscopy published guidelines in 2010 with grade A recommendation for the administration of rectal diclofenac 100 mg or indomethacin immediately before or after ERCP as post-ERCP prophylaxis [51] .…”
Section: Interruption Of Inflammatory Cascade (Anti-inflammatory): Nomentioning
confidence: 99%
“…Number needed to treat was 20. Moreover they found that in subgroup analysis, the difference remained unchanged for average-risk population [OR = 0.49 (0.28-0.85); P = 0.01] or in preventing severe PEP [OR = 0.41 (0.21-0.78); P = 0.007] [50] . The European Society of Gastrointestinal Endoscopy published guidelines in 2010 with grade A recommendation for the administration of rectal diclofenac 100 mg or indomethacin immediately before or after ERCP as post-ERCP prophylaxis [51] .…”
Section: Interruption Of Inflammatory Cascade (Anti-inflammatory): Nomentioning
confidence: 99%
“…[120][121][122][123][124][125][126][127] Validity of these conclusions could be questioned however, due to some findings which was difficult to explain or discordant to each other. 128 Several of the early PRCT reported that RNSAID (diclofenac) significantly reduced PEP in average-risk patients.…”
Section: Post-ercp Prophylaxismentioning
confidence: 99%
“…In the past decade, there have been at least six RCTs showing that NSAIDs reduce risk of PEP by 50-60 % [26][27][28][29][30][31]. In addition, there have been five meta-analyses in the past 4 years demonstrating a reduction in PEP with a number needed to treat ranging from 11 for the prevention of mild up to 34 to prevent moderate-to-severe pancreatitis [32][33][34][35][36].…”
Section: Pharmacoprophylaxismentioning
confidence: 99%